2016
DOI: 10.1177/0009922816682744
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Themes Found in Superhero Films

Abstract: Superhero films have become incredibly popular. The objective of this study was to determine the positive and negative themes found in a select number of superhero films. A total of 30 superhero films were analyzed. The average numbers of positive and negative themes were 19.4 and 29.5 mean events per hour for all included films, respectively. The most common positive themes were "assisting others/protecting the public," "positive relationships with family/friends," and "teamwork/collaboration." The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…In a recently published study examining positive and negative themes depicted in a selected number of superhero-based films, the authors concluded that the prevalence of negative themes, especially acts of violence, outweighed positive themes [11]. These acts of violence often included physical altercations, use of guns/knives/lethal weapons, bullying/intimidation/torture, murder, and demonstrating excessive anger.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study examining positive and negative themes depicted in a selected number of superhero-based films, the authors concluded that the prevalence of negative themes, especially acts of violence, outweighed positive themes [11]. These acts of violence often included physical altercations, use of guns/knives/lethal weapons, bullying/intimidation/torture, murder, and demonstrating excessive anger.…”
Section: Introductionmentioning
confidence: 99%
“…These themes are similar to those depicted in a published study analyzing themes depicted in superhero-based films. There was a 60% overlap of the 10 most common positive themes and a 70% overlap of the 10 most common negative themes when comparing superhero-based films and television shows [6]. Common positive themes found in our sample of superhero-based television shows, and not in their sample of superhero-based films, included "honesty," "justice/karma -getting what one deserves," and "forgiveness/not holding a grudge."…”
Section: Discussionmentioning
confidence: 64%
“…A recently published study examined the positive and negative themes depicted in superherobased films [6]. Based on their sample of 30 superhero-based films, the authors determined that the most common positive themes were "assisting others/protecting the public," "positive relationships with family/friends," and "teamwork/collaboration."…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed a data collection instrument that was composed of a predetermined list of positive and negative themes adapted from two previously published studies [11][12]. The data collection instrument enabled each of the five reviewers (AW, JL, KL, MM, KS) to independently document each event associated with a theme.…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been a few recently published studies examining the thematic content in top-grossing films released from 2005 to 2015 (limited to general audience (G), parental guidance (PG), and PG-13 rated films) and superhero-based films (excluding rated-R films), there have been no studies analyzing the content of top-grossing rated-R films that children and adolescents may have access to [11][12]. The objective of this study is to determine the positive and negative themes depicted in a select number of top-grossing rated-R films released from 2012 to 2017, and to compare the event rates between film genres.…”
Section: Introductionmentioning
confidence: 99%